Thermodynamics - Fermi, Enrico, 1901-1954 (Dover Books on Physics Ser., 1956)
In this classic of modern science, the Nobel Laureate presents a clear treatment of systems, the First and Second Laws of Thermodynamics, entropy, thermodynamic potentials, and much more. Calculus required.